Implementation of MMS based on Petri net - Zhang Changming; Wang Xinying; Cheng Dongling (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
IEC 61850 standard used Manufacturing Messages Specification (MMS) as its underlying communication protocol. The company standard that used in electrical system communication is not defined. It is necessary to research on the implementation of MMS protocol. In order to facilitate the implement of MMS, Petri net is used to model, analyze MMS protocol. This paper researches on the mapping rule of the conversion from Petri net model to programming code, develops a Petri net tool using object-oriented method, imports the component technology to realize the integrative conversion and then takes the domain management as an example to validate it.